Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd009218.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent iron supplementation for reducing anaemia and its associated impairments in menstruating women

Abstract: Intermittent iron supplementation in menstruating women is a feasible intervention in settings where daily supplementation is likely to be unsuccessful or not possible. In comparison with daily supplementation, the provision of iron supplements intermittently is less effective in preventing or controlling anaemia. More information is needed on morbidity (including malaria outcomes), side effects, work performance, economic productivity, depression and adherence to the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
54
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 55 publications
7
54
1
2
Order By: Relevance
“…The most common source of information on folic acid in the present study was doctors (62%), followed by newspapers (21%); this result is in accordance with previously regional data (11,12,14,18). However, the fact that most women knew about folic acid but so few used it before conception ‫املتوسط‬ ‫لرشق‬ ‫الصحية‬ ‫املجلة‬ ‫والعرشون‬ ‫الثالث‬ ‫املجلد‬ ‫العارش‬ ‫العدد‬…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The most common source of information on folic acid in the present study was doctors (62%), followed by newspapers (21%); this result is in accordance with previously regional data (11,12,14,18). However, the fact that most women knew about folic acid but so few used it before conception ‫املتوسط‬ ‫لرشق‬ ‫الصحية‬ ‫املجلة‬ ‫والعرشون‬ ‫الثالث‬ ‫املجلد‬ ‫العارش‬ ‫العدد‬…”
Section: Discussionsupporting
confidence: 90%
“…For neural tube defects, folate deficiency is considered the most important nutritional risk factor, and supplementation with preconception folic acid has been associated with a reduced risk of neural tube defects (17,18). The World Health Organization recommends that all women when first trying to conceive should take a daily supplementation of 400 μg of folic acid and continue until 12 weeks of gestation (19).According to our study, despite the high level of awareness of folic acid, only 3.2% of the women used it before conception, which is lower than in other Middle East countries including Lebanon (6.2%) (12), Egypt (8.8%) (11), Jordon (16.9%) (14) and Israel (17.6%) (1) ( Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…The review also compared intermittent iron with daily iron and showed that compared with those receiving daily iron, women receiving intermittent iron had a 26% higher risk for anemia, although final mean hemoglobin concentrations were not dissimilar. 30 Although many authors have suggested that intermittent iron administration may improve adherence, the Cochrane review did not find evidence for this. 30 A Cochrane review has also compared intermittent (1 to 3 times/wk) with daily iron in pregnancy, with no evidence of difference in infant (birth weight, gestation duration) outcomes; mothers receiving intermittent iron experienced fewer adverse effects but had lower hemoglobin concentrations and increased risk for anemia and iron deficiency at term.…”
Section: Intermittent Iron Supplementationmentioning
confidence: 99%
“…Post-menarche, females are at higher risk of developing iron deficiency because of menstrual losses, and if they do not have an adequate iron intake, this condition can progress to anemia known as iron deficiency anemia (IDA) [2].…”
mentioning
confidence: 99%